The Influence of Financial Inclusion on Credit Risks in Commercial Banks in Indonesia - Ghasarma, Reza; Muthia, Fida; Umrie, M.A. Rasyid; Sulastri, Sulastri; Arianto, Bobby (Jurnal Akuntansi dan Bisnis, 2019)
This study aims to analyze the effect of financial inclusion on credit risk in commercial banks in Indonesia. The data used are secondary data obtained from the Financial Access Survey (FAS) of the IMF and Bank Focus from 2011-2016. A total of 34 banks were sampled in this study. From the results of panel data processing, it was found that financial inclusion has a positive effect on bank credit risk, where an increase in the financial inclusion index annually causes an increase in bank credit risk. The results of this study provide insights to the government and banks to anticipate credit risk which can affect banking stability due to financial inclusion. Penelitian ini bertujuan untuk menganalisis pengaruh inklusi keuangan terhadap credit risks (risiko kredit) pada bank komersil di Indonesia. Data yang digunakan merupakan data sekunder yang didapatkan dari Financial Access Survey (FAS) IMF dan Bank Focus dari tahun 2011-2016. Sejumlah 34 bank menjadi sampel pada penelitian ini. Dari hasil pengolahan data panel, ditemukan bahwa inklusi keuangan memiliki pengaruh yang positif terhadap risiko kredit bank, dimana kenaikan indeks inklusi keuangan tiap tahunnya menyebabkan kenaikan pada risiko kredit bank. Hasil dari penelitian ini memberikan wawasan kepada pemerintah dan perbankan untuk melakukan antisipasi terhadap risiko kredit yang dapat berpengaruh kepada stabilitas perbankan akibat adanya inklusi keuangan.